Wooden Charcoal as Adsorbent Material to Capture CO\(_2\) in the CI engine Exhaust Fueled with Different Blends of Biodiesel - G. Balaji; D. Premnath; V. Rajasekar (Science and Technology: Developments and Applications Vol. 9, 2025)
A study on reducing the buildup of carbon dioxide (CO2) in the atmosphere is now necessary due to the issues with global warming and climate change brought on by greenhouse gas emissions, especially CO2. Carbon dioxide capture and storage (CCS) by absorption is a straightforward and superior technique for reducing CO2 emissions, despite the fact that several CO2 capture technologies have been developed for post-combustion processes. This study aims to reduce CO2 emissions from internal combustion engines by employing woody charcoal as an inexpensive adsorbent material. This study also encourages the transition to renewable and non-edible biofuels by demonstrating the potential of biodiesel blends made from cottonseed and neem oil. The study also explores CO2 collection methods using adsorbents to assist governments and companies in implementing cleaner energy sources. A single cylinder, four-stroke, computerized water-cooled, diesel engine with a 3.5 kW rated power was used to test the emission characteristics of the cotton seed oil and neem oil blends by varying the engine loads. This study was done for both with and without CCS. One hundred grammes of wooden charcoal was utilized in this analysis. According to the results, when operating at full load, the CCS with wooden charcoal adsorbed CO2 emissions by 11.4%. Further, the CO and HC emissions were also adsorbed by 12% and 13.75%, respectively. However, because of the back pressure, the brake thermal efficiency for CCS is somewhat reduced.